1999
DOI: 10.1182/blood.v93.5.1651.405k20_1651_1657
|View full text |Cite
|
Sign up to set email alerts
|

Clonality of Isolated Eosinophils in the Hypereosinophilic Syndrome

Abstract: The idiopathic hypereosinophilic syndrome (IHES) is a rare disorder characterized by unexplained, persistent eosinophilia associated with multiple organ dysfunction due to eosinophilic tissue infiltration. In the absence of karyotypic abnormalities, there is no specific test to detect clonal eosinophilia in IHES. Analysis of X-chromosome inactivation patterns can be used to determine whether proliferative disorders are clonal in origin. Methylation of HpaII andHha I sites near the polymorphic trinucleotide rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The historical definition of the ‘idiopathic’ HES proposed by Chusid et al in 1975 (94) empirically included: 1) a persistent eosinophilia >1.5 × 10 9 /l for longer than 6 months, or death before 6 months associated with the signs and symptoms of hypereosinophilic disease, 2) a lack of evidence for parasitic, allergic or other known causes of eosinophilia, and 3) presumptive signs and symptoms of organ involvement, including hepatosplenomegaly, organic heart murmur, congestive heart failure, diffuse or focal central nervous system abnormalities, pulmonary fibrosis, fever, weight loss or anaemia. Recent studies have demonstrated that the so‐called HES represents indeed a considerably heterogeneous group of disorders, that may result especially from clonal proliferation of lymphocytes or of the eosinophils themselves (95–100).…”
Section: Idiopathic Hypereosinophilic Syndromesmentioning
confidence: 99%
“…The historical definition of the ‘idiopathic’ HES proposed by Chusid et al in 1975 (94) empirically included: 1) a persistent eosinophilia >1.5 × 10 9 /l for longer than 6 months, or death before 6 months associated with the signs and symptoms of hypereosinophilic disease, 2) a lack of evidence for parasitic, allergic or other known causes of eosinophilia, and 3) presumptive signs and symptoms of organ involvement, including hepatosplenomegaly, organic heart murmur, congestive heart failure, diffuse or focal central nervous system abnormalities, pulmonary fibrosis, fever, weight loss or anaemia. Recent studies have demonstrated that the so‐called HES represents indeed a considerably heterogeneous group of disorders, that may result especially from clonal proliferation of lymphocytes or of the eosinophils themselves (95–100).…”
Section: Idiopathic Hypereosinophilic Syndromesmentioning
confidence: 99%
“…This contention was supported by clonality studies that used X-linked DNA analysis. 92 In contrast, the presence of clonal T H 2 lymphocytes in a subset of patients with "HES" suggests a pathogenetic heterogeneity that may include an IL-5-mediated secondary eosinophilia in the mix. 93,94 In a study of 60 patients with HES, 16 (27%) had T cells with an aberrant immunophenotype, and T-cell clonality was suggested in half of these 16 patients.…”
Section: Pathogenesis and Clinical Manifestationsmentioning
confidence: 99%
“…A few reports did provide support for a primitive myeloid disorder by showing chromosomal abnormalities adjacent to eosinophil granules 14 or skewed methylation patterns of Xlinked genes in purified granulocytes or eosinophils. 15,16 Unfortunately, applicability of these methods in HES is limited, as abnormal karyotypes are rare in this disorder, and X-linked polymorphisms can be investigated only in female patients, in the setting of a disease that predominantly affects males.…”
Section: The Myeloproliferative Variant Of Hesmentioning
confidence: 99%